Comparative Experimental Investigation of Erosion behaviour of AA2024/B4C and AA6061/B4C Metal Matrix Composites with Particulate coating. Issue 1 (January 2021) - Vijay, S; Rao, Ch Srinivasa; Laxmi Lalitha, J
Abstract: Different amounts of B4C reinforcement with 5% and 10% are coated with Nickel using Electroless coating technique and are used for reinforcement in Aluminium alloys to produce aluminium metal-matrix composites (AMC). The composites with/without nickel coating thus produced were tested for erosion rate at various pressure conditions and impinging angle. The addition of certain amount of nickel coating provides not only the wettability effect of B4C, it also increases the strength of parent materials (pure Aluminium, AA2024 and AA6061). SEM micrographs confirmed the formation of a Nickel layer on Boron Carbide. Sand erosion tests are designed using L27 orthogonal array with factors as four having three levels. External factors such as, type of matrix and the weight-percentage of particulate are selected. Internal factors viz., the pressure of the air/sand mixture and the angle of impingement. Three levels for every factor used in the experimentation and out of which, Impingement angle shows the predominant significant effect on the erosion rate. It is found that the impingement angle of level 1 (i.e. 30o) has the max influence of 39.75 % contribution on erosion rate. The Regression model is developed for estimating the erosion rate, in terms of the levels of all factor considered. From these models, it is observed that the 5% B4C reinforcement with nickel coating gives minimum erosion rate for aluminium alloys.